Soft Skill Development Model for Gen Z Students at Vocational Colleges : Perspective Human Resource Management - Jazuli Juwaini; Dingot Hamonangan Ismail; Danang Aziz Akbarona; Ria Estiana; Damdam Damiyana (Annals of Human Resource Management Research, 2026)
Purpose: This study aimed to develop a soft skills model for Generation Z students in vocational higher education. It specifically examines the influence of lecturer competence and learning motivation on improving students’ soft skills quality in the era of Industrial Revolution 4.0 and Society 5.0. Research Methodology: This study was conducted at the LP3I Polytechnic with a population of active students residing in the Jabodetabek area. A quantitative research approach was adopted. Data were collected through a structured survey using questionnaires and analyzed using statistical methods with the support of data analysis software to test the relationships among variables. Results: The results show that lecturer competence positively and significantly affects students’ soft skill development. Learning motivation also had a positive and significant effect on the quality of students’ soft skills. Furthermore, lecturer competence and learning motivation simultaneously have a positive and significant influence on improving students’ soft skills. Conclusions: This study concludes that lecturer competence and student learning motivation are key factors in enhancing the soft skills of Gen Z students in vocational education. Limitations: This study was limited to students of the Lembaga Pendidikan dan Pengembangan Profesi Indonesia (LP3I) Polytechnic in the Jabodetabek area and used a quantitative approach, which may not fully capture deeper behavioral aspects. Contributions: This study contributes to the human resource management and education literature, particularly in vocational education. This study provides practical insights for educators and institutions to improve soft skill development strategies for Generation Z students.